New Looks On Abaya as National Identity of United Arab Emirates - Alfida Marifatullah; Alfida Marifatullah (Insaniyat : Journal of Islam and Humanities, 2018)
This research discusses the new looks on the abaya which is being part of national identity in the United Arab Emirates and even more widely, abaya was accepted as an Arab culture by fashion lovers all over the world. The government boost preservation of abaya that already becomes a lifestyle of Arabs women by assigning this robe as the national dress. This research uses the qualitative method by using fashion theory from Douglas who said that anxiety is a source of fashion changes. This study shows that fashion changes due to anxiety and wants to bring change or replace it with a new one. In the United Arab Emirates, the changes of fashion occur  because the citizens want to set the abaya to be timeless culture. New looks on abaya bring out the question; How government and individuals protecting abaya from fashion changes in United Arab Emirate? The result of this study is line with the concept of Douglas about fashion; that fashion are created not only to validate or display dominant and accepted categories of identity, but also to out cultural anxiety.The changes that had already done by UAE people not only bring to the "new" UAE, but it was for preservasing culture and history of UAE.